Fiqh al-waqaf baina itarah al-qanuni wa-daurihi al-iqtisadi al-manshud =فقه "الوقف" بين إطاره القانوني ودوره الإقتصادي المنشود - Ahmed Shogar, Ibrahim Adam (2012)
The “Waqaf” is religio-economic term used in Islamic jurisprudence for donations made by individuals based on religious motives to serve the public. It usually made not in cash money but as concrete things, such as building schools or hospitals for use of public. The distinguishing feature of this private contribution in the community development is sustainability. Waqaf must be utilized in sustainable manner so that it can serve public as long as possible. Good management of Waqaf is essential for sustainability and long lasting services. Waqaf has played a crucial role to develop the society in the history of Islamic civilization through providing financial support to government and rendering direct services to the public. Many education centers, such as libraries and schools were established based on Waqaf. Therefore, this Islamic system can play a significant role in development of the contemporary Muslim communities. The major objective of this paper is to explain and highlight role of Waqaf in development of modern Muslim societies, especially in the realm of education and community cervices.